Osseointegration of Dental Implants after Vacuum Plasma Surface Treatment In Vivo - Se Hoon Kahm; Sang Hwa Lee; Youbong Lim; Hyun Jeong Jeon; Kyoung-In Yun (Journal of Functional Biomaterials)
Previous studies have highlighted the need for post-treatment of implants due to surface aging. This study investigated the effect of vacuum plasma (VP) treatment on the osseointegration of sandblasted, large grit, acid-etched (SLA) implant surfaces. The hypothesis was that VP might enhance implant stability, measured by implant stability quotient (ISQ) and histological osseointegration through bone-to-implant contact (BIC) and bone area ratio (BA) in rabbit models. Eighteen implants were either untreated or treated with VP and installed into the femurs of six rabbits, which were sacrificed after four weeks. Histological analyses of BIC and BA, along with micro-CT analysis of bone volume and ISQ, were performed. The VP-treated group showed higher levels of BA, bone volume, and ISQ, but no statistically significant differences were observed between the control and experimental groups. Despite limitations, both groups achieved better osseointegration and regeneration, warranting further studies on plasma treatment effects over varying implantation periods.